Molecular talk of adipokines in dermatological diseases - Aydin, S. (C M B Assoc, 2016)
Adipose tissue is not a passive tissue storing triglycerides, but one that releases hormones, enzymes, growth factors, and cytokines. Currently, known to release more than 600 adipokines, the adipose is an active tissue involved in energy homeostasis and serving paracrine, autocrine and endocrinal functions. Besides, some adipokines (irisin and ghrelin, for example) are synthesized in the sebaceous glands of the skin and play important roles in certain dermatological diseases. This review will provide a systemic overview of adipokines, focusing on their tissue and organ distribution, functions in biological systems, and roles in dermatological diseases. Additionally, the areas where adipokines can be used in dermatological diseases and their possible future roles will be presented.
Keywords: Adipose tissue; endocrinal function; cutaneous diseases